Satisfaction With a Family‐Focused Intervention for Mild Cognitive Impairment Dyads. Issue 4 (27th April 2016) - Lu, Yvonne Yueh‐Feng; Ellis, Jennifer; Yang, Ziyi; Weaver, Michael T.; Bakas, Tamilyn; Austrom, Mary Guerriero; Haase, Joan E.
Abstract: Purpose: This article describes satisfaction that persons with mild cognitive impairment (PwMCI) and their caregivers had with the Daily Enhancement of Meaningful Activity (DEMA) intervention. Methods: This randomized controlled pilot study compared satisfaction (usefulness, ease of use, and acceptability) with DEMA ( n = 17 dyads) to an information support (IS) control group ( n = 19 dyads). Six biweekly sessions (two in person and four by telephone) were delivered by trained nurses. Data analysis included descriptive statistics, independent‐sample t tests, and content analysis. Findings: PwMCI receiving DEMA rated their satisfaction significantly higher ( p = .033) than did the control group; there was no difference in satisfaction between caregivers across groups. Qualitative interview data supported the usefulness, ease of use, and acceptability of DEMA for both PwMCI and caregivers. Conclusions: Results documented PwMCI's satisfaction with DEMA as implemented by nurses to support PwMCI–caregiver dyads' engagement in meaningful activity. DEMA may need revision to increase satisfaction for caregivers. Clinical Relevance: The DEMA intervention was evaluated as useful, easy to use, and acceptable to PwMCI and their caregivers based on positive mean ratings. The study findings provide preliminary support of DEMA as a means to improve quality of life by helping to support patient and caregiver engagement in meaningful activities and problem solving.